2010
DOI: 10.1111/j.1740-0929.2010.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Calf production from vitrified bovine sexed embryos following in‐straw dilution

Abstract: The objective of this study was to develop an in-straw dilution method suitable for direct transfer of vitrified bovine sexed embryos. Embryo sexing was performed by molecular diagnosis. Several sexed and vitrified-warmed embryos were transferred after evaluation of morphologically embryonic survival at warming and in-straw dilution (Evaluation group). The other embryos were immediately directly transferred to recipients without first being expelled from the straws after in-straw dilution (Non-evaluation group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Lopes et al (2001) obtained comparable pregnancy rates for bisected (60%) and intact embryos (61%), while Lopatarova et al (2008) showed a 56.5% pregnancy rate after the transfer of sexed demi-embryos. Akiyama et al (2010) showed that the pregnancy rate after transferring vitrified sexed bovine embryos was of 38.7% and 34.8%. The biopsy technique used in our study involved the aspiration of several blastomeres (25 to 30% of the inner cell mass), as it was performed by slicing the embryo with a microblade.…”
Section: Resultsmentioning
confidence: 99%
“…Lopes et al (2001) obtained comparable pregnancy rates for bisected (60%) and intact embryos (61%), while Lopatarova et al (2008) showed a 56.5% pregnancy rate after the transfer of sexed demi-embryos. Akiyama et al (2010) showed that the pregnancy rate after transferring vitrified sexed bovine embryos was of 38.7% and 34.8%. The biopsy technique used in our study involved the aspiration of several blastomeres (25 to 30% of the inner cell mass), as it was performed by slicing the embryo with a microblade.…”
Section: Resultsmentioning
confidence: 99%
“…Although the pregnancy rate of the biopsied embryos was the same as that of the intact embryos, the pregnancy rates of both the frozen sexed embryos and the sexed embryos obtained from low-quality embryos were lower [3]. The biopsy-sexing of the low-quality embryos was inadequate for embryo manipulation since it could potentially reduce the viability of the embryos after ET [2, 4]. Moreover, the amplification of the male-specific DNA sequences of embryos is not financially optimal as approximately over 50% of the recovered embryos are of the undesired sex and are therefore wasted.…”
Section: Discussionmentioning
confidence: 99%
“…MOET is used with sexing equipment in dairy management for the systematic production of females. Diagnostic embryo sexing from a biopsy sample [2,3,4] and MOET with X-sorted semen [5, 6] has been previously used in the dairy farming industry.…”
mentioning
confidence: 99%
“…It has also been reported that bovine embryo vitrification and subsequent cryoprotectants dilution with the one‐step in‐straw method was comparable to that of the slow freezing method (Sano et al., ). In addition, the vitrification methods were also useful for sex‐determined embryos with low cryotolerance (Akiyama et al., ; Inaba et al., ). The vitrification and cryoprotectants dilution used in the present study might be feasible for embryos with extremely low cryotolerance.…”
Section: Discussionmentioning
confidence: 99%